PERAN PENDIDIKAN DALAM KELUARGA KRISTEN - Purba, Asmat; Sihombing, Daniel Romi (UPPM Politeknik TEDC Bandung, 2024)
Everything starts with the family. Children are born and raised and educated by both parents. The results of family education will be seen directly in the lives of children in the period of growth until they are adults. What parents sow to children, that is what will be harvested from them. As the saying goes: